Menjaga Keberlanjutan Future City Hub: Tata Kelola Ekosistem Startup dalam Kerangka Paradiplomasi Kota Kembar Jakarta–Berlin - Oktaviani Rosmala; Sulis Ariska Novrianti; Muhammad Naufal Helga Fikri; Herie Saksono (Research and Development Agency Ministry of Home Affairs, 2026)
This study identifies the contribution of the Future City Hub (FCH) to the Jakarta–Berlin sister city partnership, evaluates its role in Jakarta’s startup ecosystem, and proposes a model of sustainable governance. Using a descriptive qualitative design, we conducted a content analysis of primary, secondary, and tertiary sources. The findings suggest that globalization has shifted the dynamics of international relations, allowing local governments to act in the international arena through paradiplomacy. The Jakarta–Berlin partnership is one such arrangement, operating as an urban living lab that brings together academia, government, industry, and the public to foster innovation. Although the ecosystem surrounding the FCH has faced challenges since European Union funding ended, its host institution, the Jakarta Smart City Management Unit, has been designated a technical implementation unit operating under the regional public service agency financial management pattern, an arrangement that affords greater flexibility in financial management. The findings further indicate that the FCH has supported improvements in the quality of Jakarta’s startups by facilitating knowledge and technology transfer from Berlin. Through this model of paradiplomacy, the FCH may offer a reference point for other cities pursuing international collaboration to drive innovation in support of sustainable regional development. The study is intended to contribute to the development of policies that sustain the startup ecosystem in Jakarta.